2007
DOI: 10.1021/ja071939o
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transport and the Water Environment in Nafion Fuel Cell Membranes and AOT Reverse Micelles

Abstract: The properties of confined water and diffusive proton-transfer kinetics in the nanoscopic water channels of Nafion fuel cell membranes at various hydration levels are compared to water in a series of well-characterized AOT reverse micelles with known water nanopool sizes using the photoacid pyranine as a molecular probe. The side chains of Nafion are terminated by sulfonate groups with sodium counterions that are arrayed along the water channels. AOT has sulfonate head groups with sodium counterions that form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
280
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(304 citation statements)
references
References 69 publications
20
280
1
Order By: Relevance
“…[22][23][24][25] When confined in constrained geometries, the microscopical properties of the proton also suffer drastic changes. So, studies of PT near alumina surfaces [26] and in Nafion fuel cell membranes [27] reported changes in frequencies of vibrational motions and orientational relaxation times induced by the presence of the surface. Recently, a work based on multi-state empirical valence bond (EVB) calculations on PT in one-dimensional water chains confined in carbon nanotubes confirmed early results from Hummer et al [29] and revealed that the rate of PT inside the tubes was one order of magnitude faster than in bulk.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] When confined in constrained geometries, the microscopical properties of the proton also suffer drastic changes. So, studies of PT near alumina surfaces [26] and in Nafion fuel cell membranes [27] reported changes in frequencies of vibrational motions and orientational relaxation times induced by the presence of the surface. Recently, a work based on multi-state empirical valence bond (EVB) calculations on PT in one-dimensional water chains confined in carbon nanotubes confirmed early results from Hummer et al [29] and revealed that the rate of PT inside the tubes was one order of magnitude faster than in bulk.…”
Section: Introductionmentioning
confidence: 99%
“…The proton can then diffuse to bulk water or recombine with the excited anion to form the ROH* form in what is known as geminate recombination 33. Since the ROH* and RO −* forms have different emission wavelengths (for HPTS, 440 and 535 nm, respectively), it is relatively easy to follow their time‐resolved and steady‐state fluorescence 34, 35, 36, 37. In pure water, the proton diffuses rapidly from the photoanion, which results in a predominant RO −* species, as can be seen in the steady‐state emission spectra (Figure 2a).…”
mentioning
confidence: 99%
“…However, the decay of the ROH* form is much slower on the BSA mat, even in fully hydrated samples, which might imply that protons diffuse along the BSA mat and not into bulk water. The time‐resolved emission of the ROH* form can be used to get an estimation of the dimensionality of the proton diffusion space, where the fluorescent tail obeys a power‐law of t −d/2 , where d is the diffusion space dimensionality (see further discussion in Supporting Information) 34, 36, 37. By plotting a log–log plot (Figure S5, Supporting Information) of the lifetime corrected ROH* decay, we could estimate the fractal space dimensionality of the proton diffusion by linear fitting the first nanoseconds of the decay.…”
mentioning
confidence: 99%
“…Often protons are conducted through restricted spaces, such as in the case of protons within water channels like those of nafion membranes in hydrogen fuel cells, [25][26][27] for protons in tiny water nanopools embedded inside proteins and peptides, [28] for protons near alumina surfaces [29] or inside biomembranes. [22] Nevertheless, despite the large scientific and industrial relevance of confined protons, the mechanisms of proton conduction in confined spaces are still a largely unexplored area of research, essentially due to the limited number of experimental techniques accurate enough and also the lack of detailed predictions from the theory and simulation side.…”
Section: Introductionmentioning
confidence: 99%